2012
DOI: 10.1016/j.icheatmasstransfer.2011.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Endwall convective heat transfer for bluff bodies

Abstract: The endwall heat transfer characteristics of forced flow past bluff bodies have been investigated using liquid crystal thermography (LCT). The bluff body is placed in a rectangular channel with both its ends attached to the endwalls. The Reynolds number varies from 50,000 to 100,000. In this study, a single bluff body and two bluff bodies arranged in tandem are considered. Due to the formation of horseshoe vortices, the heat transfer is enhanced appreciably for both cases. However, for the case of two bluff bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Thereby the heat transfer coefficient over the entire area can be obtained. More details of the LCT technique for obtaining the heat transfer coefficients over an entire area can be found in [10][11][12].…”
Section: Data Reductionmentioning
confidence: 99%
“…Thereby the heat transfer coefficient over the entire area can be obtained. More details of the LCT technique for obtaining the heat transfer coefficients over an entire area can be found in [10][11][12].…”
Section: Data Reductionmentioning
confidence: 99%
“…The 3D vortical structure produced by the obstacle greatly affects heat transfer on the endwall. Wang et al [17] investigated the endwall heat transfer characteristics of forced flow past bluff bodies using liquid crystal thermography (LCT). The results indicated that due to the formation of horseshoe vortices, the heat transfer of a single bluff body and two bluff bodies arranged in tandem were both enhanced and the power [18,19] investigated the endwall heat transfer and vortices formed upstream of an airfoil using simultaneous PIV and LCT.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that an existing obstacle in the flow field always increased the heat transfer relative to an isolated one. Heat transfer caused by a bluff body such as a horseshoe vortex generator was examined experimentally by Wang et al (2012). Heat transfer was enhanced by the use of the horseshoe vortex generator in both single and tandem arrangements.…”
Section: Introductionmentioning
confidence: 99%